Is an Acetabular Cage and Cement Fixation Sufficiently Durable for the Treatment of Destructive Acetabular Metastases? - Rowell, Philip (Clin Orthop Relat Res, 2019)
BACKGROUND: Destructive bony acetabular metastases cause pain, pathological fractures, and loss of mobility. Although multiple fixation options are available, we have favored a rigid stainless steel partial pelvic cage for acetabular fixation in these patients; however, little is known about the durability of this approach. QUESTION/PURPOSES: (1) How common was loss of fixation in a small series of metastatic acetabular defects treated with an acetabular cage and cemented total hip replacement? (2) What is the implant survival free from reoperation or revision at 2 and 4 years using a competing-risks survivorship estimator in patients thus treated? (3) What complications were associated with the treatment? (4) What level of postoperative mobility was achieved? METHODS: Between 2006 and 2017, we treated all acetabular metastases that needed surgical intervention, not amenable to conventional cemented THA alone with our single technique of acetabular partial pelvic cage and cemented total hip replacement. We treated 47 hips in 46 patients whose acetabular metastasis led to acetabular collapse or who were unresponsive to nonoperative measures of radiation therapy and analgesia. Routine followup occurred at 3 and 12 months; 17 of 46 patients (37%) died before 1 year, and all other patients were followed beyond 1 year. Only one patient who remains alive has not been seen in the past 5 years. Loss of fixation was determined by radiological or clinical signs of cage loosening. Survivorship free from reoperation or revision at 2 and 4 years was determined using competing-risks analysis. We did not assess patient-reported outcomes, but we did have data on the proportion of patients who were able to ambulate in the community and if so, what assistive devices they used, which we obtained by chart review. RESULTS: One patient experienced cage loosening identified 8 years postoperatively as a result of local disease progression and has been managed with observation. No patients underwent revision for loss of acetabular fixation. The cumulative incidence of reoperation or revision was 8% at 2 years (95% CI, 3.6–12.6) and 16% at 4 years (95% CI, 9.2–23.2). Four patients had postoperative dislocations, of which three underwent reoperation. One patient developed a postoperative deep infection and underwent reoperation. One patient died within 30 days of surgery. Only one patient did not ambulate in the community postoperatively; 23 ambulated independently, 10 with the use of a walking stick and 12 using a walker. CONCLUSIONS: In this small series, we found this approach sufficiently durable to continue its use for patients with acetabular metastases with collapse or those not responding to nonoperative measures. However, comparison studies are needed to determine whether it is superior or inferior to other available alternatives. LEVEL OF EVIDENCE: Level IV, therapeutic study.